PENGARUH KARAKTERISTIK INDIVIDU, KOMUNIKASI INTERPERSONAL DAN PROFESIONALISME TERHADAP KEPUASAN KERJA PEGAWAI PADA KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI PEKANBARU - Pohan, Dewi Titianti; Ningsih, Dewita Suryati; Pramadewi, Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research was conducted in the Office of Surveillance and Customs and Excise Type Madya B Pekanbaru. This study aims to determine how the Influence of Individual Characteristics, Interpersonal Communication and Professionalism either simultaneously or partially on Employee Job Satisfaction in the Office of Surveillance and Customs and Excise Type Madya B Pekanbaru. This study is a population. The number of samples in this study were 81 respondents. The method of analysis used in this study is the method of regression analysis using SPSS version 17.00. Based on the testing that has been done, simultaneous regression test (F test) showed that the independent variables studied (Individual Characteristics, Interpersonal Communication and Professionalism) together (simultaneously) have a significant effect on the dependent variable (Employee Job Satisfaction). The magnitude of the effect that (R2) by three independent variables is jointly against the dependent variable 74%, while the remaining 26% is influenced by other variables not examined in this study. The result of the testing that has been done, the partial regression test (t test) showed that each of the independent variables studied (Individual Characteristics, Interpersonal Communication and Professionalism) had a significant effect on the dependent variable (Employee Job Satisfaction).Keywords: individual characteristics, interpersonal communication, professionalism and job satisfaction